Model ewidencji kosztów logistyki - Skrodzka, Violetta (Model of Logistic Costs' Record, 2008)
Costs constitute a starting point for any activity. Nobody can realise their aims without bearing costs. Both: some organised entity, especially an economic entity and an individual person while considering the purposefulness of the activity must accept the cost as the basic criterion for their choice when they take a decision. The costs are always incurred, but as professor A. Jarugowa points out - there are different costs, in different entities, measured for different purposes. In entities that make use of logistics while evaluating the effectiveness of logistic processes the decisive role is ascribed to logistics costs. This notion is not explicitly identified. The presented definitions being different in the scope and content lead to different results in the measurement of effectiveness. The logistics costs constitute a detailed category of the costs registered by accountancy. In order to define precisely the notion of logistics costs, it is necessary to remember about the conditions which must be fulfilled so as to be able to speak about the notion of costs itself as an objective economic category. The purpose of this article is to examine the relation between recording potentiality provided by obligatory accounting and quoted classification of logistics costs.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 132-142